Comparative evaluation of memory T cells in COVID-19 patients and the predictive role of CD4+CD8+ double positive T lymphocytes as a new marker - Kalpakci,Yasin (2020)
SUMMARY BACKGROUND: The COVID-19 pandemic has affected the entire world, posing a serious threat to human health. T cells play a critical role in the cellular immune response against viral infections. We aimed to reveal the relationship between T cell subsets and disease severity. METHODS: 40 COVID-19 patients were randomly recruited in this cross-sectional study. All cases were confirmed by quantitative RT-PCR. Patients were divided into two equivalent groups, one severe and one nonsevere. Clinical, laboratory and flow cytometric data were obtained from both clinical groups and compared. RESULTS: Lymphocyte subsets, CD4+ and CD8+ T cells, memory CD4+ T cells, memory CD8+ T cells, naive CD4+ T cells, effector memory CD4+ T cells, central memory CD4+ T cells, and CD3+CD4+ CD25+ T cells were significantly lower in severe patients. The naive T cell/CD4 + EM T cell ratio, which is an indicator of the differentiation from naive T cells to memory cells, was relatively reduced in severe disease. Peripheral CD4+CD8+ double-positive T cells were notably lower in severe presentations of the disease (median DP T cells 11.12 µL vs 1.95 µL; p< 0.001). CONCLUSIONS: As disease severity increases in COVID-19 infection, the number of T cell subsets decreases significantly. Suppression of differentiation from naive T cells to effector memory T cells is the result of severe impairment in adaptive immune functions. Peripheral CD4+CD8+ double-positive T cells were significantly reduced in severe disease presentations and may be a useful marker to predict disease severity.